Hubungan ketahanan pangan rumah tangga dengan status gizi pada balita - Safkaur, Thalia Chelsea Putri Wangloan; Sanggelorang, Yuliana; Musa, Ester Candrawati (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Food security carries out a crucial role in meeting nutritional needs because the nutrients contained in food serve to maintain health and support growth, especially in toddlers. Low food security at the household level can result in a decline in the nutritional status of toddlers, thereby increasing the risk of medical problems in this vulnerable age group. Purpose: Analyzing the relationship between household food security and nutritional status of toddlers. Method: The study design was an observational study with a cross-sectional approach. The population was 560 toddlers aged 12-59 months with a sample size of 91 toddlers selected through probability sampling and simple random sampling techniques in the Remboken Community Health Center (Puskesmas) work area, Minahasa Regency. Data were collected using the US Household Food Security Survey Module (US-HFSSM) instrument to measure household food security levels and anthropometric measurements to evaluate nutritional status based on weight-for-age (BW/A), height-for-age (H/A), and weight-for-height (BW/H). Data analysis was carried out using the Chi-square test and Fisher's exact test. Results: There was a significant relationship between household food security and nutritional status of toddlers based on the weight/age index (p value = 0.021) and height/age index (p value = 0.001). However, no significant relationship was found between household food security and nutritional status based on the weight/age index (p value = 0.221). Conclusion: Household food security in Remboken Health Center shows a significant association with nutritional status based on the weight-for-age z-score (WAZ) and height-for-age z-score (HAZ) indices, but no meaningful association with the weight-for-height z-score (WHZ) index. Suggestion: Families with toddlers should be able to utilize local foods that are more affordable, readily available, and nutritious, such as corn and freshwater fish, which are readily available. The Remboken Community Health Center (Puskesmas) can collaborate with integrated health post (Posyandu) cadres to conduct outreach activities for the community on utilizing the area around their homes as a source of family food. Keywords: Food Security; Nutritional Status; Toddlers. Pendahuluan: Ketahanan pangan memainkan peranan krusial dalam pemenuhan gizi sebab zat gizi yang terkandung dalam makanan berfungsi menjaga kesehatan dan mendukung pertumbuhan, terutama pada anak usia balita. Ketahanan pangan yang rendah di tingkat rumah tangga mampu berakibat pada penurunan status gizi balita, sehingga menghasilkan peningkatan risiko terjadinya permasalahan medis pada kelompok usia yang rentan ini. Tujuan: Untuk menganalisis hubungan antara ketahanan pangan rumah tangga dan status gizi balita. Metode: Penelitian desain observasional dengan pendekatan potong lintang. Populasi yang ditetapkan sebanyak 560 balita berusia 12-59 bulan dengan jumlah sampel sebanyak 91 balita yang dipilih melalui metode probability sampling, teknik simple random sampling di wilayah kerja Puskesmas Remboken, Kabupaten Minahasa. Data dihimpun dengan memanfaatkan instrumen US Household Food Security Survey Module (US-HFSSM) dalam rangka mengukur tingkat ketahanan pangan rumah tangga dan pengukuran antropometri dalam mengevaluasi status gizi berdasarkan indeks berat badan menurut umur (BB/U), tinggi badan menurut umur (TB/U), dan berat badan menurut tinggi badan (BB/TB). Analisis data dilakukan dengan pengujian Chi-square serta pengujian Fisher’s exact. Hasil: Adanya hubungan signifikan antara ketahanan pangan rumah tangga dan status gizi balita berdasarkan indeks BB/U (p value = 0.021) dan indeks TB/U (p value = 0.001). Namun, tidak ditemukan hubungan yang signifikan antara ketahanan pangan rumah tangga dan status gizi berdasarkan indeks BB/TB (p value = 0.221). Simpulan: Ketahanan pangan rumah tangga menunjukkan hubungan yang signifikan dengan status gizi berdasarkan indeks BB/U serta PB/U atau TB/U. Namun, tidak menunjukkan hubungan yang bermakna dengan indeks BB/PB atau BB/TB. Saran: Bagi keluarga balita, hendaknya dapat memanfaatkan pangan lokal yang lebih terjangkau, mudah untuk didapatkan dan memiliki nilai gizi seperti jagung dan ikan air tawar yang bisa didapatkan dengan mudah. Bagi instansi terkait, dapat membangun kerja sama bersama kader posyandu untuk mengadakan kegiatan penyuluhan kepada masyarakat agar dapat memanfaatkan area di sekitar rumah sebagai salah satu sumber bahan makanan keluarga. Kata Kunci: Balita; Ketahanan Pangan Rumah Tangga; Status Gizi.